Validity, Reliability and Optimal Cutoff Value of Persian Version of Arizona Sexual Experience Scale (ASEX) (male version) - Firoozeh Raisi; Hamide Sadat Sadrameli; Seyyed Tahs Yahyavi; Mohammalali Seddighi Gilani; Abbasali Nasehi; Azin Ahmadzadeh (مجله دانشگاه علوم پزشکی گیلان)
Background: Despite the high prevalence of sexual dysfunction in Iran, there are no valid and reliable Farsi questionnaires for assessing this problem. Objective: The purpose of this study is to develop the Persian version of the Arizona Sexual Experience Scale (ASEX) and evaluate its cut-off point in Iranian male patients. Methods: A total of 84 male volunteers were selected from the sexual health clinics of Imam Khomeini, Roozbeh, and Shariati hospitals in Tehran. According to the modified version of ASEX, it has 5 questions and scores ranged from 5 to 20. As part of the validity assessment, the questionnaire results were compared with clinical interviews based on DSM-V criteria. As part of the reliability assessment, 67 participants completed the questionnaire a week later. Internal consistency was determined by Cronbach's alpha, and sensitivity and specificity of the cut-off point for sexual dysfunction were determined by ROC curves. Also, the SPSS-19 software was used to conduct all statistical analyses. Results: In the study, the questionnaire scores in test and retest were highly correlated (Pearson correlation coefficient 0.990 (P<0.0001). The test and retest scores did not differ statistically significantly (p=0.766). In the Persian version of the ASEX questionnaire, Cronbach's alpha (0.831) indicated good internal consistency. The cut-off point was considered 11 based on the ROC curve, which had a sensitivity of 95% and a specificity of 100%. Conclusion: This modified Persian version of the ASEX for male patients demonstrated adequate validity and reliability for screening sexual dysfunction in Iran. The revised Persian questionnaire shows greater effectiveness than the original questionnaire due to our culture and better understanding of sexual issues in Iranian society. Lastly, an 11 out of 20 cut-off point can be used to determine sexual dysfunction. Keywords: Arizona Sexual Experience Scale; Sexual measures; Sexual inventories; Iran